Analisis Kelayakan Finansial Sistem Integrasi Sapi dan Kelapa Sawit dengan Sistem Pemeliharaan Semi Intensif (Studi Kasus pada Kelompok Tani Sarwo Sari di Desa Sari Makmur Kecamatan Pangkalan Lesung Kabupaten Pelalawan) - Yolanda Ocenia; Yusmini Yusmini; Susy Edwina (Journal of Agribusiness and Community Empowerment (JACE), 2019)
This research aims to analyze the financial feasibility and sensitivity to changes in input prices, production levels and prices of the output of a business System integration of Cow-Palm oil in Sari Makmur villagePangkalan Lesung District Pelalawan Regency Province of Riau. The research method used is the method of case studies. Data used are primary data and secondary data. The informant on this research consists of a group of farmers which is Sari Sarwo group members as many as 14 people and the number of cattle beginning as many as 51 cows ,  extension officers of Sari Makmur village, Village Unit Cooperative of Sari Makmur,and Village Unit Cooperative shop of Sari Makmur. Data analysis the criteria used was  Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C) and Internal Rate of Return (IRR). The results showed : integration efforts of cow-palm oil is worth because it has a value of NPV is positive, the value of Net B/C is greater than zero and the value of the IRR is greater than the Social Opportunity Cost of Capital (SOCC), the business is still eligible for develop in the event of a decrease in the price increase of chemical fertilizer 32.80percents, decrease in price of palm oil of 15percents, and  decrease in urine and feses price 50percents.The business is un eligible to developif in the  production of palm oil greater than47,21percents, and decrease in birth rate cow greater than53,68percents.